Male‐specific alteration in excitatory post‐synaptic development and social interaction in pre‐natal valproic acid exposure model of autism spectrum disorder. (3rd February 2013) - Kim, Ki Chan; Kim, Pitna; Go, Hyo Sang; Choi, Chang Soon; Park, Jin Hee; Kim, Hee Jin; Jeon, Se Jin; dela Pena, Ike Campomayor; Han, Seol‐Heui; Cheong, Jae Hoon; Ryu, Jong Hoon; Shin, Chan Young
Abstract Autism spectrum disorder (ASD) is a pervasive developmental disorder characterized by three main behavioral symptoms including social deficits, impaired communication, and stereotyped and repetitive behaviors. ASD prevalence shows gender bias to male. Prenatal exposure to valproic acid (VPA), a drug used in epilepsy and bipolar disorder, induces autistic symptoms in both human and rodents. As we reported previously, prenatally VPA‐exposed animals at E12 showed impairment in social behavior without any overt reproductive toxicity. Social interactions were not significantly different between male and female rats in control condition. However, VPA‐exposed male offspring showed significantly impaired social interaction while female offspring showed only marginal deficits in social interaction. Similar male inclination was observed in hyperactivity behavior induced by VPA. In addition to the ASD‐like behavioral phenotype, prenatally VPA‐exposed rat offspring shows crooked tail phenotype, which was not different between male and female groups. Both male and female rat showed reduced GABAergic neuronal marker GAD and increased glutamatergic neuronal marker vGluT1 expression. Interestingly, despite of the similar increased expression of vGluT1, post‐synaptic marker proteins such as PSD‐95 and α‐CAMKII expression was significantly elevated only in male offspring. Electron microscopy showed increased number of post‐synapse in male but not in female at 4 weeks of age. These results might suggest that the altered glutamatergic neuronal differentiation leads to deranged post‐synaptic maturation only in male offspring prenatally exposed to VPA. Consistent with the increased post‐synaptic compartment, VPA‐exposed male rats showed higher sensitivity to electric shock than VPA‐exposed female rats. These results suggest that prenatally VPA‐exposed rats show the male preponderance of ASD‐like behaviors including defective social interaction similar to human autistic patients, which might be caused by ectopic increase in glutamatergic synapses in male rats.